Who’s responsible? an immersive study to understand the violence in the Moroccan stadiums - Zizi, Ouafaê; Jiddane, Mohamed (Revue Internationale du Chercheur, 2023)
This article delves into the intricate world of stadium violence in Moroccan football, weaving a tapestry of historical analysis and insights drawn from interviews with ultras members, football federation representatives, and law enforcement officers. Through a meticulous examination, the study unravels the complex web of causes and perspectives surrounding stadium violence, shedding light on the self-perception of ultras, the challenges faced by law enforcement, and the crucial role played by the football federation. Going beyond analysis, the study proposes original and actionable recommendations, aiming to make a substantial contribution to the prevention and mitigation of stadium violence in Morocco. These recommendations, rooted in on-the-ground research and insights from key stakeholders, offer a unique and practical perspective, providing a holistic approach to addressing this multifaceted issue. In essence, the article not only illuminates the underlying dynamics of stadium violence but also seeks to pave the way for tangible solutions informed by the voices and experiences of those directly involved in the football culture of Morocco.